2013
DOI: 10.1136/sextrans-2013-051184.0995
|View full text |Cite
|
Sign up to set email alerts
|

P4.097 Is the Minimum Package of Prevention Intervention Working? Outcome of Combined Prevention Intervention Amongst In - School Youths in Kwara State, North Central, Nigeria

Abstract: Background Adolescents often lack basic reproductive health RH information, knowledge, and access to health services for RH. Many have less than favourable attitudes and do not feel comfortable to discuss RH with parents or other key adults. Objectives To assess RH knowledge, attitude and provider preference among adolescents of age 15 to 19 years. Methods A community-based cross-sectional study was conducted in Tirana Town, capital city of Albania from October 2012 to January 2013. A structured questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to the study, out-of-school youths comprising male and female were recruited and trained as peer educators who carried out activities which included community dialogue, peer educators recruitment and training, distribution of condoms, and HCT [ 37 ]. Similarly, in another report from an intervention among in-school youths in Kwara State, Nigeria, the authors reported the effectiveness of MPPI programming, which addressed behavioral change through the combination of prevention interventions targeted at individuals and communities [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study, out-of-school youths comprising male and female were recruited and trained as peer educators who carried out activities which included community dialogue, peer educators recruitment and training, distribution of condoms, and HCT [ 37 ]. Similarly, in another report from an intervention among in-school youths in Kwara State, Nigeria, the authors reported the effectiveness of MPPI programming, which addressed behavioral change through the combination of prevention interventions targeted at individuals and communities [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MPPI operationalizes the combination prevention framework in Nigeria, using information about the drivers of the epidemic relating to various target populations, emphasizing dosage and intensity on interventions, and recognizing the processes of behavior change and structural and environmental influencers of behavior [35]. Several authors have successfully implemented HIV prevention interventions based on the MPPI strategy among in-school and out-of-school adolescents, including community mobilization, outreach, advocacy, and monitoring [36][37][38]. A report from Kogi State, Nigeria, demonstrated significant success and achievement in using MPPI in an HIV prevention program.…”
Section: Discussionmentioning
confidence: 99%